Major Aspects of Land Degradation and Its Management from Various Methods: A General Review - Rahul Verma,; Priya Kushwaha,; Amit Kumar Singh,; Pallavi Dixit, (International Journal of Scientific Research in Science and Technology, 2025)
Land is an important component for any country, which provides food, shelter, fiber, and many other things that are essential for living beings. Land is a non-renewable natural resource that is degraded day by day by different types of natural and manmade practices. Land degradation is caused by different factors, including climate, natural, and anthropogenic activity can deteriorate land quality and degrade the land for agricultural practices. The agricultural sector is directly affected by land quality, which impacts agricultural production. Due to rapid changes in climatic conditions, deforestation at high risk, the desertification process, soil erosion, salinization or alkalization of soil, water logging, and depletion of organic carbon in soil are the major components of land degradation across the world. Management of land for different methods which are important to manage the activity of these components, and properly managing all the factors is responsible for soil degradation. Management of land by various methods, by covering the land with crop residue, using alternative fuel, replanting trees, and making different policies regarding land degradation. Organic farming is an important component in controlling land degradation. This review focuses on different types of soil degradation methods and their effect on crop productivity and the environment, and how it is managed by various methods.
Keywords: Land degradation; Climate change; Agriculture; Environment; Soil management